#### Answer

The expression would be $\frac{1}{(a+b)}$

#### Work Step by Step

To solve
= $(a+b)^{2}$$(a+b)^{-3}$ --> Since they have the same base, we can add the exponents.
= $(a+b)^{2+(-3)}$
= $(a+b)^{(2-3)}$
= $(a+b)^{(-1)}$
= $\frac{1}{(a+b)}$

Published by
Prentice Hall

ISBN 10:
0133281140

ISBN 13:
978-0-13328-114-9

The expression would be $\frac{1}{(a+b)}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.